2003
DOI: 10.1080/02673030304255
|View full text |Cite
|
Sign up to set email alerts
|

The Housing Consequences of Living Arrangement Choices in Young Adulthood

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…It is a set of several simultaneous binary logistic regression model with one category of dependent variable set as reference. MLM has been applied to some studies on residence choice with complicated situation (Cho, 1997;Hughes, 2003;Kim, 1992;Li, 2000;Mulder, 2003;Seko & Sumita, 2007). It is the optimal choice of measuring housing decision of the young generation in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a set of several simultaneous binary logistic regression model with one category of dependent variable set as reference. MLM has been applied to some studies on residence choice with complicated situation (Cho, 1997;Hughes, 2003;Kim, 1992;Li, 2000;Mulder, 2003;Seko & Sumita, 2007). It is the optimal choice of measuring housing decision of the young generation in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the importance of economical, educational, and demographical factors (Andrew & Meen, 2003;Asberg, 1999;Attanasio, Bottazzi, Low, & Nesheim, 2012;Bourassa, Haurin, Haurin, & Hendershot, 1994;Haurin, Hendershott, & Kim, 1994;Hughes, 2003;Mulder, 2003) such as those found in aforementioned studies, family behavior (Henretta, 1987), motivation to leave parental home (Mulder, 2003), and financial support from parents (Munro & Smith, 1989;Ost, 2012;Pickvance & Pickvance, 1995;Saunders, 1990) are discovered to be very important determinants of homeownership for young households, and these determinants influence housing decision in young adults.…”
Section: Introductionmentioning
confidence: 95%
“…Given this assumption one can see the destination of leaving home in terms of whether someone leaves home to live with or without a partner as a major determinant of the choice of housing Mulder 2003;Mulder and Hooimeijer 2002). Even after accounting for the greater resources that are likely available among couples because they frequently have two incomes, singles may be less likely to become homeowners than couples in order to remain flexible, and therefore hesitate to financially commit to homeownership.…”
Section: Leaving Home: In Which Housingmentioning
confidence: 99%
“…The findings on this association from Clark and Mulder (2000; they included mobile homes in their analysis) and Leppel (1987; she looked specifically at shared accommodation) for the United States, and from Mulder and Manting (1994), Mulder and Hooimeijer (2002) and Mulder (2003) for the Netherlands, can be summarized as follows: those who leave home to cohabit and particularly to marry are much more likely to start their housing careers as homeowners, and much less likely to start in rented accommodation and particularly in shared housing or a mobile home, than those who leave home to live without a partner. According to the same studies, those with more individual and parental resources (including parental homeownership) are more likely to start their housing careers as homeowners and less likely to start in shared accommodation or in mobile homes, whereas those enrolled in education frequently start in shared housing.…”
Section: Leaving Home: In Which Housingmentioning
confidence: 99%
“…There can Downloaded by [University of California, Los Angeles (UCLA)] at 10:12 16 May 2013 6 P. Monkkonen be long-run ramifications, however. In the Netherlands, for example, Mulder (2003) found that housing market conditions at the time when a cohort of young adults leaves the parental home has an influence on their housing situation decades later.…”
Section: Economic Development and Housing Deficitsmentioning
confidence: 99%